Terminology Matters: A Critical Exploration of Corporate Social Responsibility Terms - Baden, Denise; Harwood, Ian A. (2013)
The purpose of this paper is to highlight the importance and impact of terminology used to describe corporate social responsibility (CSR). Through a review of key literature and concepts, we uncover how the economic business case has become the dominant driver behind CSR action. With reference to the literature on semiotics, connotative meaning and social marketing we explore how the terminology itself may have facilitated this co-opting of an ethical concept by economic interests. The broader issue of moral muteness and its relation to ethical behaviour is considered. We conclude by proposing a number of important attributes for any proposed terminology relating to ethical/socially responsible/sustainable business.
Keywords: Terminology; Semiotics; Moral muteness; Instrumental CSR; Ethical footprint; Corporate Social Responsibility